2018
DOI: 10.1093/jxb/ery442
|View full text |Cite
|
Sign up to set email alerts
|

A novel discovery of a long terminal repeat retrotransposon-induced hybrid weakness in rice

Abstract: Gene activation caused by long terminal repeat retrotransposon insertion in the promoter of a newly discovered gene, Hwc3 , leads to hybrid weakness in intrasubspecific japonica rice hybrids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…A total of 5,722 F 2 plants were used for fine mapping, and the region of hwj1 and hwj2 were narrowed down to 65-kb on chromosome 1 ( Figure 5 ) and 145-kb on chromosome 11 ( Figure 6 ), respectively. In the 65-kb candidate region of hwj1 , 11 genes were predicted, and some of these are retrotransposon-like genes ( Nadir et al, 2019 ). On the other hand, the candidate region of hwj2 contains two disease resistance-related genes, thus these two genes were primary candidates for hwj2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 5,722 F 2 plants were used for fine mapping, and the region of hwj1 and hwj2 were narrowed down to 65-kb on chromosome 1 ( Figure 5 ) and 145-kb on chromosome 11 ( Figure 6 ), respectively. In the 65-kb candidate region of hwj1 , 11 genes were predicted, and some of these are retrotransposon-like genes ( Nadir et al, 2019 ). On the other hand, the candidate region of hwj2 contains two disease resistance-related genes, thus these two genes were primary candidates for hwj2 .…”
Section: Discussionmentioning
confidence: 99%
“…A high temperature mostly inhibits disease resistance (e.g., Dropkin, 1969 ). Only a few genes for hybrid weakness in rice have been cloned ( Yamamoto et al, 2010 ; Chen et al, 2014 ; Nadir et al, 2019 ). Therefore, the molecular mechanism of hybrid weakness in rice still needs to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Duplicate recessive genes such as hwb1/hwb2 (Oka, 1957), hwd1/hwd2 (Fukuoka, Namai and Okuno, 1998) and hwe1/hwe2 (Kubo and Yoshimura, 2002) are known as causal genes for F2 hybrid weakness. Further analyses of Hbd2/Hbd3 (Yamamoto et al, 2007;, Hwi1/Hwi2 (Chen et al, 2014) and Hwc3 (Nadir et al, 2019) revealed that deleterious interactions between these genes cause an autoimmune response.…”
Section: Genetic Factors Affecting Sterility and Weakness In Hybridis...mentioning
confidence: 99%
“…The identification of non-additive expression (NAE) and allele-specific expression (ASE) patterns at the gene-level is usually used to reveal the molecular mechanism of heterosis [ 9 , 10 , 11 ]. Some hybrid-weakness-associated genes have been mapped in rice [ 13 , 14 , 15 , 16 , 17 ], but there are still no reports on the study of molecular mechanisms of hybrid weakness from the perspectives of NAE and ASE. To study the molecular mechanisms underlying hybrid weakness, we performed RNA-seq with three biological replicates of the panicles at the grain-filling stage of all the hybrid and parental lines collected in E3, where four hybrids (H2, H5, H6, and H8) displayed MPHW in GYPP ( Figure 1 c).…”
Section: Introductionmentioning
confidence: 99%